The effect of heavy strength training on muscle adaptations and performance in elite cross-country skiers - Losnegard, T.; Mikkelsen, K.; Rønnestad, B. R.; Hallen, J.; Rud, B.; Raastad, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Cross-country skiing is a typical endurance sport with high reliance on maximal aerobic power. However, the introduction of sprint skiing and mass start has increased the importance of other physiological factors affecting top speed on skies, such as muscular strength and the ability to generate high power. A good correlation has been reported between maximal power output measured in a 4RM rollerboard test and sprint skiing tests in cross-country skiing (Stöggl et al 2007). In addition to have a potential role on maximal power generation and top speed on skies, heavy strength training may also reduce the energy cost of skiing and thereby also affect endurance performance (Hoff et al 1999, Østerås et al 2002). Method Eleven males (18-26 yr, VO2max; 68.3 ± 4.8 ml•kg-1•min-1) and eight females (18-27 yr, VO2max; 59.3 ± 2.9 ml•kg-1•min-1) were assigned to a strength training group (STR) (n=9) and a control group (CON) (n=10). In addition to their regular training, STR performed heavy strength training twice a week, for 12 weeks (3-4 x 4-10RM sets in three exercises for upper-body muscles and one exercise for legs). Results One repetition maximum (1RM) improved in STR both in sitting pull-down (19 %) and half squat 12 % (p<0.01), while no changes was observed in CON. Jump height was 6.2% reduced in CON (p<0.05), while no change was observed in STR. A small increase in cross sectional area (CSA) were found in m. triceps brachii for both STR and CON (p<0.05), with no change in m. quadriceps CSA. VO2max in ski-skating increased 7% in STR (p<0.01), but was unchanged in running. Work economy, evaluated from VO2 during submaximal rollerskiing was unchanged and rollerski skating time-trial performance (~5 min) improved similarly in both groups. A 100 meter sprint skiing test showed no significant changes in performance between groups. Correlation analyses from baseline (n=25) showed a strong correlation between 1RM sitting pull-down and time-trial performance and 1RM half squat and 100 meter rollerski skating performance (p<0.01). However, we were not able to observe any significant correlation between changes in 1RM and changes in any of the performance tests. Discussion A 12-week period of heavy strength training improved maximal strength in leg and upper body muscles, but had little effect on muscle cross sectional area in thigh muscles. In addition, heavy strength training added to regular endurance training improved VO2max during skating. However, we were not able to observe any statistically significant beneficial effects in time-trial performance on rollerskies. References Hoff, J., Helgerud, J., Wisløff, U. (1999). Med Sci Sports Exerc. Jun;31(6):870-7. Stöggl, T, Lindinger, S., Muller, E. (2007). Medicine & Science in Sports & Exercise. 39(7):1160-1169, July. Østerås, H., Helgerud, J., Hoff, J. (2002). Eur J Appl Physiol 88:255-263